Penerapan Metode Design Thinking Dalam Perancangan UI/UX Aplikasi My Pet Care - GURNING, AMELIA; Herdiansyah, M. Izman (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2025)
The pet shop industry is currently undergoing transformation by implementing application technology in its operations. This affects the way pet shop businesses interact with their customers. However, Papa Petshop currently still uses offline sales methods and manual payments. This method is less practical, can be time consuming and carries the risk of errors. To get an application that suits user needs, it is necessary to design an appropriate User Interface/User Experience. This research aims to design the User Interface/User Experience of the My Pet Care application at Papa Petshop using the Design Thinking method to improve service quality and provide a better experience for pet owners. This research starts from the empathize, define, ideate, prototype and test stages. Based on the Application prototype created, Usability Testing was carried out using the System Usability Scale (SUS) by getting a score of 83 with grade "A" and the "Acceptable" category.  Keywords— Design Thinking, Pet Shop, System Usability Scale (SUS), UI/UX